So tired, I can't even help you: How work-related sleep deprivation evokes dehumanization of organizational leaders and less organizational citizenship behavior - De Clercq, D.; Pereira, R. (Journal of Management and Organization, 2024)
To unpack the relationship between employees' work-induced sleep deprivation and their organizational citizenship behavior, this study details a mediating role of their propensities to dehumanize their organizational leaders, as well as a moderating role of perceived job formalization. Survey data collected from employees who work in the oil distribution sector show that a critical reason that persistent sleep problems, caused by work, reduce the likelihood that they engage in voluntary work efforts is that they treat organizational leaders as impersonal objects. Perceptions of the presence of job formalization or red tape invigorate this detrimental effect. For organizational practitioners, this study accordingly reveals a notable danger for employees who have trouble sleeping due to work: They do not take on extra work that otherwise could add to their organizational standing. This counterproductive dynamic is particularly salient when employees believe that their work functioning is constrained by strict organizational policies and guidelines.